ChemInform Abstract: Sequential Deoxyfluorination Approach for the Synthesis of Protected α, β, γ‐Trifluoro‐δ‐amino Acids. Issue 13 (1st April 2014) - Cheerlavancha, Raju; Lawer, Aggie; Cagnes, Marina; Bhadbhade, Mohan; Hunter, Luke
Abstract The synthesis of two novel δ‐amino acid derivatives (VII) and (X) containing three vicinal fluorine atoms placed stereospecifically in the backbone is detailed.